2017
DOI: 10.1097/01.aoa.0000527011.77477.1c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epidural Labor Analgesia With Low Concentrations of Local Anesthetics on Obstetric Outcomes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: (Anesth Analg. 2017;124(5):1571–1580) Epidural analgesia may slightly prolong the second stage of labor and increase the instrumental birth rate, especially when high concentrations of local anesthetics are used. Consequently, low concentrations of local anesthetics (LCLAs) have become popular for epidural labor analgesia to help mediate second stage labor. The authors of the present study conducted a systematic review and meta-analysis to compare the effects of epidural analgesia with LCLAs with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
2
16
1
2
Order By: Relevance
“…Historically, epidurals consisted of concentrated local anesthetics (0.25%-0.5% bupivacaine) to achieve pain relief during labor, however these high concentrations were associated with an unacceptably high incidence of motor block in analgesia [50]. In another meta-analysis, no differences in assisted vaginal, cesarean delivery or duration of labor were found with dilute labor epidural analgesia compared to nonepidural analgesic options [52]. Similarly, a recent large randomized study found similar duration of the second stage of labor and spontaneous vaginal delivery rates when comparing 0.08% ropivacaine with 0.4 mg/ml sufentanil to placebo administered with the onset of the second stage of labor [53].…”
Section: Optimal Epidural Solutionmentioning
confidence: 99%
“…Historically, epidurals consisted of concentrated local anesthetics (0.25%-0.5% bupivacaine) to achieve pain relief during labor, however these high concentrations were associated with an unacceptably high incidence of motor block in analgesia [50]. In another meta-analysis, no differences in assisted vaginal, cesarean delivery or duration of labor were found with dilute labor epidural analgesia compared to nonepidural analgesic options [52]. Similarly, a recent large randomized study found similar duration of the second stage of labor and spontaneous vaginal delivery rates when comparing 0.08% ropivacaine with 0.4 mg/ml sufentanil to placebo administered with the onset of the second stage of labor [53].…”
Section: Optimal Epidural Solutionmentioning
confidence: 99%
“…When low concentration EA was compared with nonepidural analgesia, Wang et al could not demonstrate any difference in instrumental delivery rates or prolonged second stage of labour in a 2017 published metaanalysis. 26 Importantly, the authors stated that also low-quality studies were included, with an overall decline in quality and certainty of the conclusions drawn. If EA was directly related to the tremendously higher rate of instrumental delivery in our study population, it may be due to divergence of practice from universally accepted guidelines in modern obstetric anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings differ from recent literature, describing an acceptable prolongation of the second stage of labour 23,36 or even no effect with low concentrations. 26 Still, the data of the National Registry gives no information on distinct stages and the timepoint of EA, hindering meaningful comparisons. The low EA rates let assume, that the choice of epidural use is more likely due to underlying circumstances of labour progress than the women's choice, making it more likely that EA was used in already prolonged labour cases.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural analgesia can form the dissociative block because low concentration of local anesthetics and opioids in the epidural space can effectively block some sympathetic and sensory nerves without affecting the motor nerves. This treatment can induce an analgesic effect with the retention of motor function, which is particularly applicable to labor analgesia [2].…”
Section: Introductionmentioning
confidence: 99%